2022
DOI: 10.1117/1.jmi.9.4.044003
|View full text |Cite
|
Sign up to set email alerts
|

One-step iterative reconstruction approach based on eigentissue decomposition for spectral photon-counting computed tomography

Abstract: Purpose: We propose a one-step tissue characterization method for spectral photon-counting computed tomography (SPCCT) using eigentissue decomposition (ETD), tailored for highly accurate human tissue characterization in radiotherapy. Methods:The approach combines a Poisson likelihood, a spatial prior, and a quantitative prior constraining eigentissue fractions based on expected values for tabulated tissues. There are two regularization parameters: α for the quantitative prior, and β for the spatial prior. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…One-step methods resolve the image by formulating the problem as a large-scale optimization to extract image properties directly from spectral sinogram data. A few of those methods were proposed over the last decade, first for DECT (Cai et al 2013, Long and Fessler 2014, Jolivet et al 2021, later for spectral PCCT focused on K-edge imaging (Foygel Barber et al 2016, Weidinger et al 2016, and recently for spectral PCCT in the context of radiotherapy (Simard and Bouchard 2022). Such approaches are currently the most promising for simultaneously correcting major reconstruction artefacts (e.g.…”
Section: Mect Image Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…One-step methods resolve the image by formulating the problem as a large-scale optimization to extract image properties directly from spectral sinogram data. A few of those methods were proposed over the last decade, first for DECT (Cai et al 2013, Long and Fessler 2014, Jolivet et al 2021, later for spectral PCCT focused on K-edge imaging (Foygel Barber et al 2016, Weidinger et al 2016, and recently for spectral PCCT in the context of radiotherapy (Simard and Bouchard 2022). Such approaches are currently the most promising for simultaneously correcting major reconstruction artefacts (e.g.…”
Section: Mect Image Reconstructionmentioning
confidence: 99%
“…With experimental data of tissue substitutes, they showed that the RMSE on ρ s decreases by a factor of 1.9 using the Bayesian technique. Another study by Simard et al (2022) demonstrated the robustness of the Bayesian approach with photon-counting CT (4 energy bins) using experimental measurements with tissue substitutes and 2 contrast agents.…”
Section: Mect Image Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these techniques are computationally more demanding and require an efficient optimization algorithm. Several algorithms have been investigated for one-step reconstruction: nonlinear conjugate gradient (Cai et al 2013, Simard andBouchard 2022), separable quadratic surrogates (SQS) (Long and Fessler 2014, Weidinger et al 2016, Mechlem et al 2017, Tilley et al 2019, Lee et al 2022, Liu et al 2022 or algorithms based on proximal operators such as ADMM (Jolivet et al 2020, Schmidt et al 2022, Chambolle-Pock (Barber et al 2016, Chen et al 2021 or VMILa (Tairi et al 2020). A previous comparative study (Mory et al 2018) has demonstrated that SQS combined with Nesterov's momentum is an efficient algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed at demonstrating the image quality improvement of one-step approaches over a prereconstruction MD method, called two-step in the following. Existing one-step algorithms have been compared to two-step methods (Mechlem et al 2017, Simard andBouchard 2022) but, to our knowledge, no study has rigorously compared the image quality of one-step and two-step material decomposition strategies. In this study, a one-step algorithm and a two-step algorithm were selected from the literature and implemented.…”
Section: Introductionmentioning
confidence: 99%